Aplikasi Metode Tahlili, Ijmali, dan Maudhu’iy (Tematik) - Rijal, Amru; Tasbih, Muhammad; Z, Zaenab (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This paper provides a comprehensive discussion of three principal methods in hadith studies: the tahlili (analytical), ijmali (concise/global), and maudhu’iy (thematic) approaches. These methodologies are essential for contextual and applicable understanding of hadith. The tahlili method emphasizes a deep analysis of a single hadith, examining both its chain of narration (sanad) and its content (matan); the ijmali method offers a concise and general understanding of hadith; while the maudhu’iy method compiles and analyzes multiple hadiths related to a single theme to produce a holistic thematic comprehension. This research employs a qualitative approach using library research with descriptive and comparative analysis of definitions, application procedures, strengths, and limitations of each method. The paper also presents concrete examples of their application. The findings indicate that each method has distinct advantages and can be strategically combined depending on the research objectives. Methodological understanding is crucial for students and scholars in producing relevant and authoritative hadith studies in response to contemporary challenges.